Bananas (Musa AAA): Importance, production and trade in Covid-19 times - Martínez-Solórzano, Gustavo E. (2021)
Introduction. Bananas are currently the most consumed fruits in the world, and considered strategic crops in food security in many countries. However, in the event of a COVID-19 pandemic, side effects are generated that affect its economic activity worldwide. Objective. To point out the most significant features of bananas in relation to their economic and productive importance in the face of the conditions generated by the COVID-19 pandemic, as well as the current phytosanitary threats as limiting factors for their production. Development. Bananas are the basis of the economy and diet of many countries, occupying an important place in international production and trade, being the most exported fruit, mostly represented by triploid AAA subgroup Cavendish. Its consumption provides vitamins, minerals, and other elements with medicinal properties, such as lectin that acts as a broad-spectrum antiviral agent. However, at present there have been disruptions in its supply, which affects all elements of the production chain, as a result of the situation caused by COVID-19. Conclusions. The coronavirus pandemic has generated collateral effects that involve various areas such as the production and trade of bananas, and are associated with social isolation and restricted mobility. However, it is considered that bananas will continue to be the most important fruit within this sector, standing out among the fastest growing crops in agriculture, despite the conditions caused by COVID-19 and the existence of many uncertainties caused by emerging diseases and climatic disturbances, which can affect the economic and productive environment.